ALCHEMIES OF PLACE IN TUNGA’S GEOPOETIC EXPRESSIONS - Souza Júnior, Carlos Roberto Bernardes de (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1051, 2021)
Relevant protagonist of Brazilian contemporary Art, Tunga built installations of provocative character that employed poetics and materials that are originated from telluric elements. This essay seeks to decipher geopoetic connections between earth and place as expressed in the metaphors of Tunga’s installations presented in Instituto Inhotin and at the 33th São Paulo Art Biannual. Based on the creative return in Geography and informed by the field of phenomenological studies, geopoetic expressions of ‘X-Estudo’ (2009) and ‘Sem Título’ [from ‘La Voie Humide’ Series] (2014) artworks in their capacity to unravel existential spaces. It is comprehended that cosmos expanded by earthly worlds elucidate interconnections at the hearth of primal relations to place. The subject-place-artwork reciprocity, thus, can potentialize understandings of the geographicality of being-in-the-world.